Role of Content Marketing in Stimulating the Consumer Expectations – A Study at Karnataka State (International Journal of Food and Nutritional Sciences, 2022)
Today’s marketing completely dominated by customers. The customers become king and decide the ways of marketing approaches and techniques. One of the most important & considerable development in this decade is awareness and knowledge regarding the accessibility, availability, storing, usage and disposable the product due to revolution in Science and Technology. Digital mode of operations makes easier to gather required and timely information’s. In this regard, the marketing industry and associates are using various approaches such as Customer relationship management, Public relation management, Pre and Post purchase analysis etc. Content Marketing is a new age of marketing and supplement to the traditional marketing. The use of new age of marketing provide completely different dimension for existing marketing environment and help the companies in order to reach out Expectation, Perception and Engagement levels. Hence the present study is undertaken to enumerate the Scope and Importance Content Marketing in the Indian marketing environment.